V2X communication system with non-orthogonal multiple access: outage performance perspective - Tu-Trinh Nguyen; Dinh-Thuan Do (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
To achieve low-latency and high-reliability (LLHR) for applications in the vehicle-toeverything (V2X) networks, the non-orthogonal multiple access (NOMA) based Long Term Evolution (LTE)-based is introduced a promising technology. NOMA-V2X provides higher spectrum efficiency compared with the orthogonal multiple access (OMA) based V2X. This study propose two-way relay assisted NOMA-V2X transmission by exploiting amplify-and-forward (AF) and full-duplex. We derive expressions of outage probability to evaluate performance of two vehicles and to improve the quality of service (QoS) for the device with the poor channel conditions. These expressions are further verified by Monte-Carlo simulations.